A bilateral N2pc (N2pcb) component is elicited by search targets displayed on the vertical midline. (9th December 2019) - Doro, Mattia; Bellini, Francesco; Brigadoi, Sabrina; Eimer, Martin; Dell'Acqua, Roberto
Abstract: The study of visually elicited event‐related potentials (ERPs) detected at posterior recording sites during visual search has enormously advanced our knowledge about how and when visuo‐spatial attention locks onto one or more laterally presented target objects. The N2pc component to lateral targets has been pivotal to further our understanding of the mechanisms and time course of target selection in visual search. However, the N2pc cannot track visuo‐spatial attention deployment to targets displayed along the vertical midline. Here, we introduce a new ERP marker (N2pcb component) that is elicited during the selection of such midline targets. In line with retinal and callosal projections from striate to ventral extrastriate cortex, this component reflects an enhanced negativity elicited by midline targets over both posterior hemispheres. By comparing the attentional selection of lateral and midline targets in a singleton search condition and a feature search condition, we show that the N2pcb is triggered at the same time as the N2pc to lateral targets, and shows the same onset latency difference between singleton and feature search. We conclude that the N2pcb and N2pc components reflect the same attentional target selection processes in visual search. Abstract : The N2pc component of ERPs elicited by visual search arrays is the most popular means to detect the allocation of visuo‐spatial attention to laterally displayed target objects. Contrary to the widespread view that N2pc is practically "blind" to target objects displayed along the vertical midline, this is the first demonstration that a bilateral N2pc can be elicited by such targets. This newly discovered ERP hallmark of attention allocation along the vertical midline, termed N2pcb, paves the way to future visual search studies in which ERP monitoring of attention allocation is not constrained by target position in visual arrays.